The Implementation of Augmented Reality and First Person Method of Promotional Media in Kemang Pratama Housing Bekasi - Muhammad Atthalariq; Didik Setiyadi (Jurnal Mantik, 2021)
The promotional media used in the Kemang Pratama Bekasi housing complex uses brochures with 2D images, causing a lack of promotion of the housing. And if you want to see the condition or appearance of the house, you have to come to the location of the house in the Kemang Pratama Bekasi housing complex as a clear picture. But by using the implementation model of Augmented Reality and First Person Mode as a media for promoting housing in Kemang Pratama, Bekasi, it makes it easier for buyers to see the condition and appearance of the house in terms of home specifications, because it can display a 3D-shaped house using a smartphone camera as an initial image before seeing the house to the location. So with this technology it becomes more effective and efficient in terms of time. Augmented Reality is used to view the exterior with a brochure (as a marker) which is scanned using a camera and First person mode to see the interior of the house.